Clofazimine: A Promising Inhibitor of Rabies Virus - Wu, Jiajing; Cao, Shouchun; Lei, Shan; Liu, Qiang; Li, Yinghong; Yu, Yueyang; Xie, Hui; Li, Qianqian; Zhao, Xiaoqiang; Chen, Ruifeng; Huang, Weijin; Xiao, Xinyue; et al. (Frontiers in Pharmacology, 2021)
With an almost 100% mortality rate, rabies virus (RABV) infection is a global concern. Limited post-exposure prophylaxis and lack of an effective treatment necessitate novel antiviral therapies against RABV. Here, using a high-throughput screening (HTS) method developed in our lab, 11 candidates with anti-RABV activity were identified from a library of 767 clinical drugs. Clofazimine (CFZ), an anti-leprosy drug, displayed an EC50 of 2.28 μM, and SI over 967 against RABV. Investigations into the underlying mechanisms revealed that CFZ targeted viral membrane fusion at the early stages of virus replication. Moreover, CFZ and Clofazimine salicylates (CFZS) exhibited elevated survival rates in vivo, compared with the positive control T-705. Thus, this study revealed CFZ as a promising drug against RABV infection.